Serum indoleamine 2,3-dioxygenase level and diagnostic value in patients with rosacea - Merve Sena Odabasi; Serkan Yazici; Guven Ozkaya; Emel Bulbul Baskan; Arzu Yilmaztepe Oral (Wolters Kluwer Medknow Publications, 2023)
Background: Indoleamine 2,3-dioxygenase (IDO), an enzyme in the first step of tryptophan catabolism, plays a role in the pathogenesis of various malignancies and inflammatory diseases. Although its pathogenesis is unclear, vascular dysregulation and chronic inflammation are the most common culprits for rosacea. Objectives: The aim of this study is to evaluate the relationship between IDO and rosacea and whether there is a correlation with disease severity. Methods: Fifty-two patients with rosacea and 29 healthy volunteers were recruited. The patients were grouped according to severity stage, period, and subtype of the disease. Serum IDO levels were measured with enzyme-linked immunosorbent assay. Results: Serum IDO levels were significantly higher in the patients with rosacea compared to the healthy controls (P < 0.001) and were significantly higher in the patients in remission period and with papulopustular type rosacea compared to the controls (P = 0.002 and P = 0.001, respectively). The serum IDO levels of the female rosacea patients were higher than those of the healthy female controls (P < 0.001). When the diagnostic value of the parameter was investigated, it was observed that the serum IDO level has high sensitivity (83.3%) and specificity (76.1%), with a cutoff value of 47.1 ng/mL for female rosacea patients. Conclusion: IDO was found to increase in rosacea patients. With the high specificity and sensitivity observed, especially in female patients, IDO may be a supporting parameter in the diagnosis of rosacea.